Substance P antagonist improves both obesity and asthma in a mouse model - Ramalho, R. (2021)
Evidence suggests a causal relationship between obesity and asthma; however, the underlying mechanisms remain unknown. Substance P (SP), involved in neurogenic inflammation by acting through its receptor NK1-R, seems to participate in obese–asthma phenotype in mice. To evaluate the effect of a selective substance P receptor antagonist on a mouse model of diet-induced obesity and asthma. Diet-induced obese Balb/c mice were sensitized and challenged with ovalbumin (OVA) and treated with a selective NK1-R antagonist or placebo. Serum glucose, insulin, IL-6, resistin, and OVA-specific IgE levels were quantified. A score for peribronchial inflammation in lung histology was used. Cells were counted in bronchoalveolar lavage fluid. Adipocyte sizes were measured. Ovalbumin-obese mice treated with NK1-R antagonist had lower weight (P = 0.0002), reduced daily food intake (P = 0.0021), reduced daily energy intake (P = 0.0021), reduced surface adipocyte areas (P < 0.0001), lower serum glucose (P = 0.04), lower serum insulin (P = 0.03), lower serum IL-(P = 0.0022), lower serum resistin (P = 0.0043), lower serum OVA-specific IgE (P = 0.035), and lower peribronchial inflammation score (P < 0.0001) than nontreated OVA-obese mice. We observed an interaction between obesity, allergen sensitization, and treatment with NK1-R antagonist for metabolic and systemic biomarkers, and for allergen sensitization and bronchial inflammation, showing a synergy between these variables. In an experimental model of obesity and asthma in mice, NK1-R blockade improved metabolic and systemic biomarkers, as well as allergen sensitization and bronchial inflammation. These positive effects support a common pathway in the obese–asthma phenotype and highlight SP as a target with potential clinical interest in the obese–asthma epidemics.